Phase Segregated Pt–SnO2/C Nanohybrids for Highly Efficient Oxygen Reduction Electrocatalysis. Issue 51 (13th December 2020) - Guan, Jingyu; Zan, Yongxi; Shao, Rong; Niu, Jin; Dou, Meiling; Zhu, Baoning; Zhang, Zhengping; Wang, Feng
Abstract: Strengthening the interfacial interaction in heterogeneous catalysts can lead to a dramatic improvement in their performance and allow the use of smaller amounts of active noble metal, thus decreasing the cost without compromising their activity. In this work, a facile phase‐segregation method is demonstrated for synthesizing platinum–tin oxide hybrids supported on carbon black (PtSnO2 /C) in situ by air annealing PtSn alloy nanoparticles on carbon black. Compared with a control sample formed by preloading SnO2 on carbon support followed by deposition of Pt nanoparticles, the phase‐segregation‐derived PtSnO2 /C exhibits a more strongly coupled PtSnO2 interface with lattice overlap of Pt (111) and SnO2 (200), along with enhanced electron transfer from SnO2 to Pt. Furthermore, the PtSnO2 active sites show a strong ability to degrade reactive oxygen species. As a result, the PtSnO2 /C nanohybrids exhibit both excellent activity and stability as a catalyst for the oxygen reduction reaction, with an overall performance which is superior to both the control sample and commercial Pt/C catalyst. This phase‐segregation method can be expected to be applicable in the preparation of other strongly coupled nanohybrids and offers a new route to high‐performance heterogeneous catalysts for low‐cost energy conversion devices. Abstract : The phase‐segregation‐derived PtSnO2 /C exhibits strong interaction at PtSnO2 interface, which produces a synergetic effect associated with the electron‐enriched Pt NPs and compressed lattice, along with the more effective ROS degradation. As a result, the PtSnO2 /C shows excellent initial ORR activity and long‐term stability.